Micropropagation and Microtuber Induction in Dioscorea wallichii Hook.f. - Thankappan, Sreeja; Abraham, K (JOURNAL OF ROOT CROPS, 2013)
An in vitro protocol was developed for the micropropagation and microtuber induction in Dioscorea wallichii for the first time using nodal explant at Central Tuber Crops Research Institute, Thiruvananthapuram, India. MS medium with Benzyl Amino Purine (BAP) at 2 Î¼M recorded the best response for shooting with the development of 2.6 shoots with an average shoot length of 8.6 cm and 11.8 nodes on each shoot which occurred within 5.6 days of inoculation. Kinetin (Kin) was found to be less effective for shooting. The addition of Naphthalene Acetic Acid (NAA) (1 Î¼M) along with cytokinin (1-6 Î¼M) also reduced shooting. Among the different levels of sucrose tested, MS medium with 8% sucrose was the best for shooting with the initiation of a single shoot of 11.8 cm length and with 9.6 nodes each within 17 days of inoculation. Microtuber induction was recorded in the presence of BAP (1-2 Î¼M) and Kin (2 - 4 Î¼M) in the medium. Addition of 8% sucrose produced the biggest microtubers with 5.28 cm length from the basal region in 4.4 months. Hence MS medium with BAP (2 Î¼M) was adjudged as the best medium for shooting, whereas, MS basal medium with 8% sucrose was found to be the best for shooting and microtuber induction in D. wallichii.